Streptococcus pneumoniae Endopeptidase O (PepO) Elicits a Strong Innate Immune Response in Mice via TLR2 and TLR4 Signaling Pathways - Zhang, Hong; Kang, Lihua; Yao, Hua; He, Yujuan; Wang, Xiaofang; Xu, Wenchun; Song, Zhixin; Yin, Yibing; Zhang, Xuemei (Frontiers in Cellular and Infection Microbiology, 2016)
Interaction between virulence factors of streptococcus pneumoniae and innate immune receptors elicits host responses through specific signaling pathways during infection. Insights into the signaling events may provide a better knowledge of the starting events for host-pathogen interaction. Here we demonstrated a significant induction of innate immune response elicited by recombinant streptococcus pneumoniae endopeptidase O (rPepO), a newer pneumococcal virulence protein, both in vivo and in vitro. Intratracheal instillation of rPepO protein resulted in significant increase of cytokines production and neutrophils infiltration in mouse lungs. TLR2 or TLR4 deficient mice subjected to rPepO treatment showed decreased cytokines production, reduced neutrophils infiltration and intensified tissue injury as compared with WT mice. Upon stimulation, cytokines TNF-α, IL-6, CXCL1 and CXCL10 were produced by peritoneal exudate macrophages (PEMs) in a TLR2 and TLR4 dependent manner. rPepO- induced cytokines production was markedly decreased in TLR2 or TLR4 deficient PEMs. Further study revealed that cytokines induction relied on the rapid phosphorylation of p38, Akt and p65, not the activation of ERK or JNK. While in TLR2 or TLR4 deficient PEMs the activation of p65 was undetectable. Taken together, these results indicate for the first time that the newer pneumococcal virulence protein PepO activates host innate immune response partially through TLR2 and TLR4 signaling pathways.